Students’ Test Anxiety in English Foreign Learners in Indonesian Context - Syafrizal, Syafrizal; Fadilah, Nita (Universitas Nusantara PGRI Kediri, 2018)
Due to the increasing demand of proficiency in English, every school and institution has also demanded their students to learn English. To identify whether the students have understood the subject matter, tests are being conducted to measure the students’ understanding. Several studies agreed and confirmed that tests can make the students feel anxious. As an affective factor, test anxiety has been investigated a lot. The current research focuses on test anxiety as the major affective factors. Thus, this research aims to find out the test anxiety level of students at Senior High School level, along with its relationship with the students’ gender and major. Moreover, the causes of the test anxiety were investigated according to the students’ own perceptions through semi-structured interview. To gather the data for this mixed-method research, the Test Anxiety Scale and semi-structured interview were conducted. The overall result showed that the students had moderate level of test anxiety. Female and science class students tend to be more anxious than the male and social students are. The factors of the test anxiety mentioned by the participants are English understanding, test preparation, time limit, pressure to prove oneself, and test procedure.